The Canadian Labour Bibliography = La Bibliographique du mouvement ouvrier canadien, 1986-1987 - Lonardo, Michael; Sweeney, Robert C. H. (Labour / Le Travail, 1991)
Compilation of recent English/French publications on Canadian labour history that emphasize the period 1800-1975. Materials pertaining to the post-1975 period may also be included, although more selectively. [See the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.]